Pengaruh Citra Merek dan Kesadaran Merek Terhadap Keputusan Pembelian HP Iphone di Kota Mataram - Supratman; Ridho Rafqi Ilhamalimy (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
In Indonesia itself, currently the competition for dual camera technology smartphones can be said to be dominated by Asian manufacturers, especially from mainland China. Oppo, Vivo, Huawei, LG, Asus, Lenovo are some of the Asian vendors that have so far competed in the market with dual camera smartphones. The purpose of this study was to determine the effect of brand image and brand awareness on purchasing decisions for iPhone brand mobile phones. The quantitative descriptive research method with a sample size of 97 people. Data analysis was carried out using SPSS Statistical Program for Social Sciences 2.7. The results of the study found that brand image had a positive and significant effect on purchasing decisions for iPhone brand mobile phones, brand awareness had a positive and significant effect on purchasing decisions for iPhone brand mobile phones.